Longitudinal changes in MRI markers in a reversible unilateral ureteral obstruction mouse model: Preliminary experience. Issue 4 (22nd October 2013) - Haque, Muhammad E.; Franklin, Tammy; Bokhary, Ujala; Mathew, Liby; Hack, Bradley K.; Chang, Anthony; Puri, Tipu S.; Prasad, Pottumarthi V.
<x xml:space="preserve">Abstract</x> Purpose To evaluate longitudinal changes in renal oxygenation and diffusion measurements in a model of reversible unilateral ureteral obstruction (rUUO) which has been shown to induce chronic renal functional deficits in a strain dependent way. C57BL/6 mice show higher degree of functional deficit compared with BALB/c mice. Because hypoxia and development of fibrosis are associated with chronic kidney diseases and are responsible for progression, we hypothesized that MRI measurements would be able to monitor the longitudinal changes in this model and will show strain dependent differences in response. Here blood oxygenation level dependent (BOLD) and diffusion MRI measurements were performed at three time points over a 30 day period in mice with rUUO. Materials and Methods The studies were performed on a 4.7T scanner with the mice anesthetized with isoflurane before UUO, 2 and 28 days postrelease of 6 days of obstruction. Results We found at the early time point (∼2 days after releasing the obstruction), the relative oxygenation in C57Bl/6 mice were lower compared with BALB/c. Diffusion measurements were lower at this time point and reached statistical significance in BALB/c Conclusion These methods may prove valuable in better understanding the natural progression of kidney diseases and in evaluating novel interventions to limit progression. J. Magn. Reson. Imaging 2014;39:835–841. © 2013 Wiley Periodicals, Inc.